Tuning the Electronic Properties of 2H-MoS2/C Anode Materials for Sodium-Ion Batteries via Zn Doping - Zhang, P.; Wang, X.; Yang, Y.; Liu, Y.; Hou, X.; Lu, Chunsheng (2023)
The molybdenum disulfide/carbon (2H-MoS2/C) composite material with a high discharge capacity has aroused much research interest in sodium-ion batteries (SIBs), but the poor intrinsic electronic conductivity and lack of intralayer active sites of 2H-MoS2 limit further improvement of its electrochemical performance. In this paper, Zn doping has been applied to optimize the electronic properties of 2H-MoS2/C. By using first-principles calculations, we have systematically investigated the effects of Zn doping on the physicochemical properties and Na storage performance of 2H-MoS2/C. It is shown that Zn doping can effectively change the intrinsic electrical conductivity, enhance the activity of sites, generate more active sites, and strengthen the interfacial stability. The enhanced electrochemical activity contributes to the Na adsorption on the C surface, interface, and MoS2 surface of 2H-MoS2/C as well as the Na diffusion kinetics on the C surface and interface. The enhanced electron transfer and ionic adsorption/diffusion capability promote the rate performance. These findings provide a significant theoretical basis for the experimental design of high-performance 2H-MoS2/C anode materials for SIBs.